Book Review: Soft Skills and Transformations of Work – Theoretical and Empirical Approaches - Alevizos, Antonios (HAPSc Policy Briefs Series, 2025)
The collective volume "Soft Skills and Transformations of Work" constitutes a substantial contribution to the ongoing dialogue about the future of work and education. It convincingly demonstrates that soft skills are not merely complementary to technical ones but form a fundamental pillar of employability, social cohesion, and resilience in the face of contemporary challenges. This is a volume worth reading not only by the academic community but also by policymakers and practitioners, as it provides valuable insights and analytical tools for understanding and addressing the social and occupational transformations of our time.